(untitled) (Canadian Medical Education Journal, 2014)
Background: Intimidation and harassment (I&H) have been longstanding problems in residency training. These behaviours continue to be prevalent, as evidenced by the 2012 Canadian Association of Interns and Residents (CAIR) National Resident Survey. More than seven in ten (72.9%) residents reported behaviour from others that made them feel diminished during their residency. We conducted a literature review to identify other surveys to determine the prevalence, key themes, and solutions to I&H across residency programs. Method: PubMed and MEDLINE searches were performed using the key words “intimidation,” “harassment,” “inappropriate behaviour,” “abuse,” “mistreatment,” “discrimination,” and “residency.” The search was limited to English language articles published between 1996 and 2013, and to papers where ten or more residents were surveyed or interviewed. Results: A total of ten articles were reviewed. Our findings showed that I&H continue to be highly prevalent with 45-93% of residents reporting this behaviour on at least one occasion. Verbal abuse was the most predominant form; staff physicians and nurses tended to be the dominant source. Residents reported that I&H caused significant emotional impact; however, very few incidents of inappropriate behaviour were reported. Very few solutions to I&H were proposed. Conclusions: I&H in residency education continue to be common problems that are under-reported and under-discussed. The opportunity exists to improve efforts in this area. Definitions of what incorporates I&H should be revisited and various educational and structural initiatives should be implemented.